Assessing attachment status in adults with intellectual disabilities: the potential of the Adult Attachment Projective Picture System. Issue 2 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to explore the potential of the Adult Attachment Projective Picture System (AAP) as a measure of attachment state of mind in adults with intellectual disabilities. The AAP is a free response picture system method of assessing patterns of adult attachment with established validity and reliability in community and clinical samples.Design/methodology/approach – The paper reports on five cases of adults with intellectual disabilities who were administered the AAP as part of routine clinical work. The AAP administration procedure was modified to take account of the participants' intellectual disabilities.Findings – It was possible to code and classify each AAP using the established coding and classification system. The authors coded four cases blind to each other's classification; they agreed on classifications for three cases and reached consensus on the fourth. The AAP analysis showed strong correspondence with case history material.Originality/value – The AAP demonstrates the potential to assess attachment state of mind in adults with intellectual disabilities and is the first developmental measure of attachment status that has shown potential in this population. The paper discusses clinical application of the AAP and directions for future research. Acknowledgements : Plymouth Community Healthcare (CIC) was formerly part of NHS Plymouth. The authors wish to thank; Dr Judith McBrien, who arranged funding for the first author's AAP training via the Developmental Disabilities Research and Education Group (hosted by Plymouth University); Professor Malcolm West, who co‐facilitated the AAP training seminar with Dr George; Ms Kay Hughes who has supported the first author in maintaining research time; all of the clients who consented to participate in this study.